2013
DOI: 10.1155/2013/915436
|View full text |Cite
|
Sign up to set email alerts
|

Bauhinia variegataLeaf Extracts Exhibit Considerable Antibacterial, Antioxidant, and Anticancer Activities

Abstract: The present study reports the phytochemical profiling, antimicrobial, antioxidant, and anticancer activities of Bauhinia variegata leaf extracts. The reducing sugar, anthraquinone, and saponins were observed in polar extracts, while terpenoids and alkaloids were present in nonpolar and ethanol extracts. Total flavonoid contents in various extracts were found in the range of 11–222.67 mg QE/g. In disc diffusion assays, petroleum ether and chloroform fractions exhibited considerable inhibition against Klebsiella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(144 citation statements)
references
References 33 publications
6
133
0
5
Order By: Relevance
“…As it was mention before, Epicatechin was the most abundant compound in both by-products, peels are also majoritarian in different sort of B-type epicatechin dimer, trimer, tetramers and flavonol glycosides. On one hand Hollman et al (1999) reports higher antioxidant activity on aglycones compared with glycosides, while Mishra et al (2013) point out the difference between dimers, trimers, tetramers, heptamers and hexamers specificity on their properties as an antioxidants. These and other interaction could explain the differences obtained in the antioxidant activity between P. americana by-products, but in order to obtain better comprehension on this phenomena, more analysis have to be performed.…”
Section: Antioxidant Capacity Of P Americana By-productsmentioning
confidence: 99%
“…As it was mention before, Epicatechin was the most abundant compound in both by-products, peels are also majoritarian in different sort of B-type epicatechin dimer, trimer, tetramers and flavonol glycosides. On one hand Hollman et al (1999) reports higher antioxidant activity on aglycones compared with glycosides, while Mishra et al (2013) point out the difference between dimers, trimers, tetramers, heptamers and hexamers specificity on their properties as an antioxidants. These and other interaction could explain the differences obtained in the antioxidant activity between P. americana by-products, but in order to obtain better comprehension on this phenomena, more analysis have to be performed.…”
Section: Antioxidant Capacity Of P Americana By-productsmentioning
confidence: 99%
“…Because of their capacity to chelate metal ions (iron, copper, etc. ), flavonoids also inhibit free radical generation Mishra et al, 2013b). The flavonoid heterocycle contributes to antioxidant activity by permitting conjugation between the aromatic rings and the presence of a free 3-OH.…”
Section: Fig 1 Binding Sites For Trace Metals Where Men+ Indicates mentioning
confidence: 99%
“…Because of their capacity to chelate metal ions (iron, copper, etc. ), flavonoids also inhibit free radical generation Mishra et al, 2013b). Quercetin in particular is known for its iron-chelating and iron-stabilizing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-compounds containing antioxidant potential have the capacity to inhibit carcinogenesis (Wang et al, 2011;Firdaus et al, 2013). In earlier studies, apigenin, quercetin, and luteolin were shown to inhibit cancer cell proliferation (Mishra et al, 2013a(Mishra et al, , 2013bFotsis et al, 1997). Moreover, phenolics have been observed to postpone or inhibit the progression of various diseases by preventing peroxidation of lipid membranes .…”
Section: Mechanisms Of Action Of Phytochemicalsmentioning
confidence: 99%